Implementation of Sexual Violence Reporting System Services (SIPORAS) as an Implementation of Permendikbud No. 30 of 2021 at Universitas Malikussaleh - Yesy Afrilia; Khalsiah; Rizky Putra Fhonna; Gilang Ramadhan; Andra Munandar (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
This study discusses the implementation of the sexual violence reporting system (SIPORAS) service as the implementation of Permen No. 30 of 2021 at Universitas Malikussaleh. On the basis of the Minister of Education and Culture 30/2021 in providing efforts to create a safe, healthy, and comfortable campus from various forms of gender-based violence, especially sexual violence to produce human resources. Indonesia that is superior, humane and has character. Several previous studies have shown that many students are aware of forms of sexual violence on campus. However, not all students who know information about the prevention of sexual violence cases and do not know about institutions that specifically handle sexual violence cases, while student understanding is important in order to involve students to confirm cases of violence at the college level and create a safe and friendly campus and avoid various kinds of sexual violence cases. Therefore, there is a need for research related to the application and socialization of the use of online-based Sexual Violence Reporting System Services (SIPORAS) in the higher education environment, namely Malikussaleh University which is managed by the University PPKS Task Force Institute and the Center for Gender Studies and Counseling.